Measurement of jet multiplicity distributions in t(t)over-bar production in pp collisions at root s=7TeV - Chatrchyan, S. (2014)
The normalised differential top quark-antiquark production cross section is measured as a function of the jet multiplicity in proton-proton collisions at a centre-of-mass energy of 7 TeV at the LHC with the CMS detector. The measurement is performed in both the dilepton and lepton+jets decay channels using data corresponding to an integrated luminosity of 5.0 fb(-1). Using a procedure to associate jets to decay products of the top quarks, the differential cross section of the t (t) over bar production is determined as a function of the additional jet multiplicity in the lepton+jets channel. Furthermore, the fraction of events with no additional jets is measured in the dilepton channel, as a function of the threshold on the jet transverse momentum. The measurements are compared with predictions from perturbative quantum chromodynamics and no significant deviations are observed.